Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/aic.17036
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating energy scaling between atomic and molecular adsorbates in the presence of solvent

Abstract: Condensed phase reactions have recently attracted increased interest, but principles for efficiently screening and designing catalyst materials through computations are lacking. In this study, we examine the applicability of energy correlations between adsorbed surface species, which have been instrumental in accelerating the computational design of catalyst materials in gas-phase contexts, in various representations of a condensed phase reaction environment. We perform detailed density functional theory calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…As an upshot, such corrections to adsorption free energies by fully implicit solvation models are typically small for the prototypical adsorbates of interest in aqueous environments, in particular for *H and *O, while being slightly larger for *OH, *OOH, or *H 2 O, maybe reaching up to several hundred millielectronvolts for the dipolar species. By and large, this seems to agree with the results of calculations with explicit solvent, 409,417,419,420 but this is most likely just due to fortuitous error cancellation in such free energy differences rather than evidence for the accuracy of present-day implicit solvation models and their existing parametrizations. For instance, the previously mentioned problematics of volume-dependent, nonelectrostatic cavity terms is lifted when computing adsorption energies, as they largely cancel in the total energy difference.…”
Section: Computational Hydrogen Electrodesupporting
confidence: 68%
“…As an upshot, such corrections to adsorption free energies by fully implicit solvation models are typically small for the prototypical adsorbates of interest in aqueous environments, in particular for *H and *O, while being slightly larger for *OH, *OOH, or *H 2 O, maybe reaching up to several hundred millielectronvolts for the dipolar species. By and large, this seems to agree with the results of calculations with explicit solvent, 409,417,419,420 but this is most likely just due to fortuitous error cancellation in such free energy differences rather than evidence for the accuracy of present-day implicit solvation models and their existing parametrizations. For instance, the previously mentioned problematics of volume-dependent, nonelectrostatic cavity terms is lifted when computing adsorption energies, as they largely cancel in the total energy difference.…”
Section: Computational Hydrogen Electrodesupporting
confidence: 68%
“…As an upshot, such corrections to adsorption free energies by fully implicit solvation models are typically small for the prototypical adsorbates of interest in aqueous environments in particular for *H and *O, while being slightly larger for *OH, *OOH or *H 2 O, maybe reaching up to some hundred meVs for the dipolar species. By and large, this seems to agree with the results of calculations with explicit solvent, 389,397,399,400 but this is most likely just due to fortuitous error cancellation in such free energy differences rather than evidence for the accuracy of present-day implicit solvation models and their existing parametrizations. More detailed analysis of the contributions points out that an arguably most important correction to existing schemes would be to account for so-called competitive solvent adsorption in the cavitation grand potential.…”
Section: Computational Hydrogen Electrodesupporting
confidence: 68%
“…43,44,402 This view would be supported by the strong correlations with the OH/H 2 O adsorption properties of the substrate. 44 Note, however, that competitive solvent adsorption is also not appropriately considered in a wide range of simple explicit solvation strategies, 373,400 while it is generally questionable anyway whether the limited trajectories obtained in the dynamic simulations can really faithfully mimic thermodynamic equilibrium. On the implicit solvation side, there are some hints that more substrate-specific models such as the SCSS model using soft-sphere atomic cavities might constitute a way forward while not compromising other observables.…”
Section: Computational Hydrogen Electrodementioning
confidence: 99%
“…The Grimme’s D3 dispersion correction scheme was used to describe the van der Waals interaction. The solvent effect on scaling relationships were not taken into account as a previous study showed that no significant change that can alter the scaling relationships has been found as the solvent effect was incorporated . More details regarding the adopted computational models, calculation of various energy values, and selection of energetic descriptors are given in the Supporting Information.…”
Section: Computation Methodsmentioning
confidence: 99%